UTILIZATION OF COMPUTER BASED PAI LEARNING MEDIA, MICROSOFT POWERT POINT AND INTERNET MEDIA - Mayarisa, Diyah; Khurtum, Baidowi (INCARE, International Journal of Educational Resources, 2023)
The urgency of learning media is to overcome the limitations of experience, to concretize abstract concepts, to overcome the limitations of space and time, to have direct interaction with the environment, to produce uniformity of observations, to instill true, concrete and realistic basic concepts, to arouse motivation and stimulate children to learn, to arouse the desires and interests of the teacher and provide an integral experience Classification of learning media, namely visual media, audio, audio visual, print, models, reality, computers in the learning process and multimedia. Computer-based learning media is the use of computers as a medium for conveying learning information, practice questions, feedback, and scores of students' answers. Computer-based learning media consists of: PowerPoint presentations, CD/DVD/ Interactive Learning Multimedia, learning videos and the internet. Computer-based learning supports curriculum implementation, helps efforts to increase interest in learning, and becomes a complement to learning resources. The presence of computer technology in learning only acts as a complement, addition (supplement) or tool for teachers.